Enhanced functionalities of biomaterials through metal ion surface modification - Tao, Yujie; Nishio Ayre, Wayne; Jiang, Liming; Chen, Siyu; Dong, Yuqi; Wu, Lin; Jiao, Yilai; Liu, Xiaohan (Frontiers in Bioengineering and Biotechnology, 2025)
The development of new artificial biomaterials for bone defect repair is an ongoing area of clinical research. Metal ions such as zinc, copper, magnesium, calcium, strontium, silver, and cerium play various roles in bone tissue regeneration in the human body and possess a range of biochemical functions. Studies have demonstrated that appropriate concentrations of these metal ions can promote osteogenesis and angiogenesis, inhibit osteoclast activity, and deter bacterial infections. Researchers have incorporated metal ions into biomaterials using various methods to create artificial bone materials with enhanced osteogenic and antibacterial capabilities. In addition to the osteogenic properties of all the aforementioned metal ions, Zn, Sr, and Ce can indirectly promote osteogenesis by inhibiting osteoclast activity. Cu, Mg, and Sr significantly enhance angiogenesis, while the antibacterial properties of Zn, Cu, Ag, and Ce can reduce the likelihood of infection and inflammation caused by implanted materials. This paper reviews the mechanisms through which metal ions promote bone tissue growth and improve the antibacterial activity of biomaterials. It also summarizes common loading methods on the surface of biomaterials with different metals and highlights the potential clinical applications of these new artificial bone materials.